Implications of DSM-5 for the diagnosis of pediatric eating disorders - Limburg, K.; Shu, C.; Watson, H.; Hoiles, K.; Egan, Sarah (John Wiley & Sons, Inc., 2018)
© 2018 Wiley Periodicals, Inc. Objective: The aim of the study was to compare the DSM-IV, DSM-5, and ICD-10 eating disorders (ED) nomenclatures to assess their value in the classification of pediatric eating disorders. We investigated the prevalence of the disorders in accordance with each system's diagnostic criteria, diagnostic concordance between the systems, and interrater reliability. Method: Participants were 1062 children and adolescents assessed at intake to a specialist Eating Disorders Program (91.6% female, mean age 14.5 years, SD=1.75). Measures were collected from routine intake assessments. Results: DSM-5 categorization led to a lower prevalence of unspecified EDs when compared with DSM-IV. There was almost complete overlap for specified EDs. Kappa values indicated almost excellent agreement between the two coders on all three diagnostic systems, although there was higher interrater reliability for DSM-5 and ICD-10 when compared with DSM-IV. Discussion: DSM-5 nomenclature is useful in classifying eating disorders in pediatric clinical samples.